Through Pains And Gains: Measures Of 21st Century Skills And Sense Of Self-Efficacy Of Alternative Learning System (Als) Learners - Zulueta, Ma. Cristina E.; Girlin Bag-ao, Girlin Bag-ao; Bayucca, Shallimar A.; Brombuela, Glenn B.; Cajurao, Garci Gil V.; Canlas, Alden P.; Mendoza, Maria Vanessa S.; Roque III, Myron Willie B.; Sagun, Angelita T.; Caparas, EdD, Ma. Editha R. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
For several years, illiteracy, poverty, and deprivation were the worst adversary of the Philippine Government. One of the greatly affected sectors of illiteracy and poverty is the education sector. The Department of Education (DepEd) has experienced large amounts of drop-outs and out-of-school youth and adults due to poverty. For the Department to alleviate this concern, the Alternative Learning System (ALS) was established. ALS offers basic schooling for all persons who wish to return to school in a way that fits their personal needs and situation. Hence, this study assessed and extrapolated ALS learners with their 21st-century skills and its correlation to their sense of self-efficacy. Using a descriptive-correlational design, the researchers wanted to establish a link between and among variables. The findings of the study revealed moderate acquisition of 21st-century skills among ALS’ learners. Their sense of self-efficacy was also noted to be high. Further analysis revealed that, ALS learners’ acquisition of 21st century skills significantly correlated to their sense of self-efficacy. It is recommended that ALS teachers should provide more activities that will further enhance and strengthen the local and global awareness of ALS learners. Also, possible extension of the study could be undertaken to draw the general picture of the ALS learners as to their skills and sense of self-efficacy.